Application of rice straw as biosorption for removal of dyeing aqueous solution and for improving the fastness property of dyed fabric - P Choomjaihan; S Meethawon (My University, 2019)
Fabric dyeing industry has been widely located throughout Thailand and the treatment of polluted water after dyeing process has been a primary focus. The objectives of this study were to study on factors affecting treated (acidic and alkaline) and non-treated rice straw on aqueous solution quality and fastness quality of dyed fabric. The results showed that increasing the absorption time increased the percentage of color removal efficiency until it was stable at 80 min soaking time onward. The alkaline treated rice straw gave the highest percentage of the percentage of color removal efficiency. Determination on the fastness quality of dyed fabric; it was found that, non-treated, acidic treated and alkaline treated rice straw potentially removed the excessed color form the dyed fabric which the fastness quality of dyed fabric was improved.
Keywords: Rice straw; Biosorption; Dyeing and Modifying Textile Fibers